Lectotypification of Dioscorea zingiberensis (Dioscoreaceae), an endemic species from China - Pagare, Ravikiran S.; Wilson, Arisdason; Janarthanam, Malapati K. (Bangladesh Journal of Plant Taxonomy, 2016)
Not available. Bangladesh J. Plant Taxon. 23(1): 87-89, 2016 (June)